Immature stages, host plants and natural enemies of Henosepilachna implicata (Mulsant) (Coleoptera: Coccinellidae) with DNA sequence data and a new synonym and notes on some Indian species of Epilachnini - Poorani, J.; Booth, R. G.; Gracy, R. Gandhi; Anuradha, C.; Thanigairaj, R.; Swathi, R. S. (Zootaxa, 2021)
Life stages of Henosepilachna implicata (Mulsant), an economically important species of Epilachnini in India, are documented and illustrated. Mitochondrial DNA sequence data is provided for the first time for H. implicata with additional details on its host plants, distribution, and natural enemies. Its similarities and differences with other common pestiferous Henosepilachna spp. in India such as H. vigintioctopunctata (F.), H. septima (Dieke) and H. pusillanima (Mulsant) are discussed. Epilachna circularis Korschefsky, 1933 is found to be conspecific with H. implicata and is reduced to a junior synonym of the latter (new synonym). Notes are given on the distribution and natural enemies of some other species of Epilachnini of the Indian region.